Melatonin: A review of its potential functions and effects on neurological diseases - Gunata, M.; Parlakpinar, H.; Acet, H.A. (Revue neurologique, 2020)
The aging process is not univocal, both body and brain age. Neurological disorders are a major cause of disability and death worldwide. According to the Global Burden of Disease Study 2015, neurological diseases are the second most common cause of death and 16.8% of total deaths are caused by neurological diseases worldwide. Neurological disease deaths have risen 36% worldwide in 25 years. Melatonin is a neuroregulator hormone that has free radical scavenger, strong antioxidant, anti-inflammatory, and immunosuppressive actions. These major properties of melatonin can play an important role in the pathophysiological mechanisms of neurological diseases. In addition, melatonin is necessary for circadian rhythm. Studies have shown that melatonin levels are low in people with neurological diseases. Both preventive and therapeutic effects of melatonin are known for many diseases, including neurological diseases (e.g., Alzheimer's disease, Parkinson's disease, multiple sclerosis, amyotrophic lateral sclerosis, Huntington's disease, epilepsy, headache, etc.). Based on all these reasons, clinical trials of melatonin were performed and successful results were declared. In this review, biological and chemical knowledge of melatonin, its experimental effects, and the clinical impact on patients with neurological disorders were described. According to all of the beneficial results obtained from experimental and clinical trials, melatonin may have a prophylactic and therapeutic effect on neurological diseases. Strong collaboration between neurologists and health service policy makers is needed to encourage use of melatonin in the patients suffering from neurological diseases. Melatonin may be the solution we have been looking for.